2023
DOI: 10.1038/s41467-023-42183-9
|View full text |Cite
|
Sign up to set email alerts
|

Next-generation CRISPR gene-drive systems using Cas12a nuclease

Sara Sanz Juste,
Emily M. Okamoto,
Christina Nguyen
et al.

Abstract: One method for reducing the impact of vector-borne diseases is through the use of CRISPR-based gene drives, which manipulate insect populations due to their ability to rapidly propagate desired genetic traits into a target population. However, all current gene drives employ a Cas9 nuclease that is constitutively active, impeding our control over their propagation abilities and limiting the generation of alternative gene drive arrangements. Yet, other nucleases such as the temperature sensitive Cas12a have not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…In line with these properties of Cas12a, Víctor López Del Amo et al reported that Cas12a gene drive produced resistant alleles in 5-8% of the target population 39 .…”
Section: Discussionmentioning
confidence: 85%
See 4 more Smart Citations
“…In line with these properties of Cas12a, Víctor López Del Amo et al reported that Cas12a gene drive produced resistant alleles in 5-8% of the target population 39 .…”
Section: Discussionmentioning
confidence: 85%
“…In this proof-of-concept study, we showed HSV1 viruses could act as gene drive vectors, allowing both Cas9 and Cas12f1 gene drives to invade into viruses with WT alleles. Taking advantage of the fast replication rate of HSV1, spread of gene drive reached plateau in one week, a speed not achieved by any other organisms tested so far 13,16,17,39 . Cas12f1 gene drives effectively converted almost all viruses and rarely produced resistant variants.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations